Modeling and simulation of the hydrogen blended gas-electricity integrated energy system and influence analysis of hydrogen blending modes. (15th January 2022) - Zhou, Dengji; Yan, Siyun; Huang, Dawen; Shao, Tiemin; Xiao, Wang; Hao, Jiarui; Wang, Chen; Yu, Tianqi
Abstract: Blending hydrogen into the natural gas network has a pivotal role in absorbing large-scale renewable energy sources and alleviating the supply-demand contradiction between the electricity and natural gas. This work focuses on the modeling and simulation of hydrogen blended gas-electricity integrated energy system and the influence analysis of hydrogen blending modes. The coupling characteristics between the power grid and natural gas network are fully considered in the modeling process. The simulation analyses are performed based on the real-scale natural gas network, renewable energy generation capacity and real user loads to compare the influence of hydrogen blending modes on the natural gas network pressure, flow rate and network loss. Results show that hydrogen blending in the upper line of natural gas network is superior to that in the lower line, and the concentrated hydrogen blending strategy is better than the dispersed one. Hydrogen blending behavior will certainly increase the loss of the natural gas network. The closer the hydrogen blending location is to the natural gas pipeline outlet, the smaller the natural gas network loss is, which can reduce the loss by about 36.5 %. The work provides a profitable reference for the hydrogen blended gas-electricity integrated energy system to absorb the surplus renewable energy sources. Highlights: A hydrogen-blended GE-IES model is built and filled the blank of domain modelling. The model is verified by a real natural gas network and multi renewable energy sources. The effects of different hydrogen blending modes on natural gas network are analyzed. It proved the feasibility to absorb large-scale renewable energy by hydrogen blending.